2017
DOI: 10.1021/acs.bioconjchem.7b00595
|View full text |Cite
|
Sign up to set email alerts
|

Designing Dendron–Polymer Conjugate Based Targeted Drug Delivery Platforms with a “Mix-and-Match” Modularity

Abstract: Polymeric micellar systems are emerging as a very important class of nanopharmaceuticals due to their ability to improve pharmacokinetics and biodistribution of chemotherapy drugs, as well as to reduce related systemic toxicities. While these nanosized delivery systems inherently benefit from passive targeting through the enhanced permeation and retention effect leading to increased accumulation in the tumor, additional active targeting can be achieved through surface modification of micelles with targeting gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…As the general chemical methodologies involved in the synthesis of telodendrimers were becoming available, the biological perspective of their applications became the next focus [ 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 ]. As noted by Newkome in 1985, it was the search for an architectural outline with the ability to form micelles that inspired the scientific community about these hybrid structures.…”
Section: Telodendrimersmentioning
confidence: 99%
“…As the general chemical methodologies involved in the synthesis of telodendrimers were becoming available, the biological perspective of their applications became the next focus [ 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 ]. As noted by Newkome in 1985, it was the search for an architectural outline with the ability to form micelles that inspired the scientific community about these hybrid structures.…”
Section: Telodendrimersmentioning
confidence: 99%
“…In a recent study, Sanyal and coworkers reported a modular micellar system for delivery of docetaxel. An AB type diblock dendron polymer conjugate was used to introduce targeting RGD (arginine-glycine-aspartic acid) peptides onto NP surface ( Scheme 10 ) [ 92 ]. The peptide targeting group containing diblock copolymer was composed of a linear PEG polymer appended with an acetal protected hydrophobic polyester dendron at one end and the cyclic RGD peptide targeting unit at the other end.…”
Section: Nano-sized Aggregates From Polymer-dendron Triblock Conjumentioning
confidence: 99%
“… Illustration of drug loaded, RGD targeted micellar NPs via “Mix-and-Match” approach employing AB and ABA type dendron−polymer constructs. Reprinted with permission from [ 92 ]. Copyright (2017) American Chemical Society.…”
Section: Schemesmentioning
confidence: 99%
“…[14][15][16][17][18] Acidic pH, glutathione, reactive oxygen species (ROS), and enzymatic activities are typical examples of endogenous stimuli, while light and temperature are exogenous stimuli. [19][20][21] The response to these stimuli has led to more precise control over the dissociation or disintegration of smart PDDS. [22][23][24] In particular, enzyme-responsive systems are especially promising in that enzymes are great catalysts with high selectivity towards specific substrates.…”
Section: A C C E P T E D Mmentioning
confidence: 99%